ERK, Akt, and STAT5 are Differentially Activated by the Two Growth Hormone Receptor Subtypes of a Teleost Fish (Oncorhynchus Mykiss) - Kittilson, Jeffrey; Jones, Evan; Sheridan, Mark (Frontiers in Endocrinology, 2011)
Previously, we found that the teleost fish, rainbow trout, possesses two growth hormone receptor (GHR) subtypes that display distinct ligand binding and agonist-induced regulation features. In this study, we used Chinese hamster ovary-K1 cells stably transfected individually with the two trout GHR subtypes, GHR1 and GHR2, to elucidate receptor-effector pathway linkages. Growth hormone (GH) stimulated rapid (5-10 min) phosphorylation of ERK, Akt, JAk2, and STAT5 in both GHR1- and GHR2-expressing cells; however; STAT5 was activated to a greater extent through GHR1 than through GHR2, whereas ERK and Akt were activated to a greater through GHR2 than through GHR1. Although blockade of the ERK pathway had no effect on the activation of Akt, inhibition of PI3k-Akt partially prevented activation of ERK, suggesting cross-talk between the ERK and PI3K-Akt pathways. JAK2 inhibition completely blocked activation of ERK, Akt, and STAT5, suggesting that all of these pathways link to GHR1 and GHR2 via JAK2. These findings establish important receptor-effector pathway linkages and suggest that the GHR subtypes of teleost fish may be functionally distinct.